Pendampingan Kader Posyandu Lansia di Suka Raya - Sulaiman Sulaiman; Lagut Sutandra; Yeni Vera; Anggriani Anggriani (Journal of Dedicators Community, 2018)
Elderly integrated service pos is an integrated service post for elderly people (elderly) in a certain area that has been agreed by society. Cadres integrated service post have an important role in mobilizing elderly to come to integrated service post. In  Village of Suka Raya the number of elderly as many as 338 people from the total population 4291 people. Activity Posyandu elderly in Villege of Suka Raya less desirable by elderly who really need basic health services, so many elderly in the Village of Suka Raya experiencing health disturbances. This community service uses methods of counseling, training, application and assistance in the use of infrared addressed at cadres integrated service post in Village of Suka Raya. The aim of this Community Service is that integrated service post cadres understand and are able to provide maximum service to the elderly who come to integrated service post. The results of this Community Service show that there is an increase in elderly visits to integrated service post by 30%. It is expected that integrated service post cadres and elderly families can participate actively in helping to increase the elderly visit to the integrated service post of elderly.